Organizational Values and Culture as Drivers of Sustainable Competitive Advantage in Private Senior High Schools - Paulus Sunarjo; Ahmad Mulyana; Dudi Permana; Erna Sofriana Imaningsih (Politeknik Siber Cerdika Internasional, 2026)
Background: Private senior high schools in Indonesia face intensifying competition driven by digital transformation, educational globalization, and rising stakeholder expectations. In this context, sustainable competitive advantage can no longer be built solely on physical resources but must be grounded in intangible strategic assets that are valuable, rare, inimitable, and non-substitutable. Objective: This study analyzes the role of organizational values and culture in building sustainable competitive advantage in private senior high schools. Methods: The research employs a qualitative approach with a multiple-case study design involving two leading private high schools in Jakarta. Data were collected through in-depth interviews (six informants from each school), field observation, and document analysis, and validated using triangulation techniques. Results: The findings reveal that both private high schools develop strong organizational values as the foundation of their strategic management practices, which are subsequently implemented through structured student development programs. Despite differences in cultural orientation—one emphasizing discipline and academic excellence and the other focusing on holistic education and character development—both schools successfully translate their values into distinctive programs that enhance student outcomes and institutional reputation. Furthermore, continuous evaluation mechanisms and experiential learning activities play a significant role in sustaining program effectiveness. Conclusion: This study contributes to the literature by providing empirical evidence that organizational culture and value-based strategies function as critical intangible resources that drive sustainable competitive advantage in educational institutions. The findings also offer practical implications for school leaders in designing culturally grounded strategies to enhance school competitiveness.